Revision of the genus Leptohyphes Eaton (Ephemeroptera: Leptohyphidae) in North and Central America - Baumgardner, D. E.; Mccafferty, W. P. (Zootaxa, 2010)
Changes to the taxonomy of North and Central America Leptohyphes (Ephemeroptera: Leptohyphidae) include the following. Leptohyphes ferruginus and L. apache are revalidated. The adult stage of L. ferruginus is diagnosed based upon subimagos and a reared female adult and a partially emerged male adult. Leptohyphes piraticus is placed as a junior synonym of L. ferruginus. Leptohyphes vulturnus and L. zelus are shown to be junior synonyms of L. zalope. Leptohyphes hispidus, L. lumas, L. spiculatus, and L. succinus are placed as junior synonyms of L. apache. Leptohyphes castaneus, L. tarsos, and L. consortis are placed as junior synonyms of L. sabinas. Leptohyphes brunneus is placed as a junior synonym of L. musseri. Leptohyphes lestes is newly reported from the USA. Numerous problems and errors asssociated with original descriptions of Leptohyphes species are discussed. A taxonomic key is presented to all known larval stages of North and Central American species of Leptohyphes.